Financial Literacy and Financial Well-being of Business School Faculties: A Study in the Context of Nepal (Quest Journal of Management and Social Sciences, 2025)
Background: Financial literacy plays a vital role in achieving financial well-being through informed financial decisions. Globally, many studies highlight its importance, linking knowledge, attitude, and behavior to financial stability. However, in Nepal, especially among business school faculties, limited research has examined how financial literacy influences their overall financial well-being.Purpose: The purpose of this paper is to examine the effect of financial literacy on the financial well-being of business school faculties in Nepal.Design/methodology/approach: The study employed a positivist research philosophy and adopted a causal comparative research design, utilizing cross-sectional data. A total of 407 business school faculties were surveyed using purposive sampling, a non-probability sampling technique. A five-point Likert scale structured questionnaire was employed. Data was collected through field surveys and analyzed using descriptive statistics, measurement modeling, and structural equation modeling (SEM) with Smart PLS 4.1.1.2.Findings: The results confirm that financial literacy significantly impacts financial well-being. Strong financial knowledge, a positive financial attitude, and effective financial behavior all improve well-being among business school faculty members.Conclusion: The study concludes that enhancing financial literacy improves the financial well-being of business school faculty members. Strengthening knowledge, attitude, and behavior in financial matters is crucial for long-term financial security. The findings offer valuable insights for policymakers and educational institutions to develop effective training and support programs.Keywords: Financial Literacy, Financial Knowledge, Financial Attitude, Financial Behavior, Financial Well-being, Business School Faculties